Critical Analysis of the Musnad of Abu Dawud al-Tayalisi: Perspectives from Classical to Contemporary Scholars - Muhammad Jamil; Rizzaldy Satria Wiwaha (al-Afkar, Journal For Islamic Studies, 2025)
This study analyzes Musnad Abu Dawud al-Tayalisi, the oldest compilation of hadith compiled by Abu Dawud al-Tayalisi (133–204 AH/750–819 AD) with the musnad method, which is the grouping of hadiths based on the companions of the prophets. The purpose of this study is to explore the contribution of this book to the development of hadith science, analyze the structure of sanad and its narration, and assess its relevance in the study of modern hadith. The method used is a literature study with a historical-critical approach, including verification of sanad, evaluation of the validity of hadiths, and comparison with other hadith compilations. Musnad al-Tayalisi is recognized by classical scholars such as Imam Ahmad bin Hanbal as an important reference. The book is also appreciated in modern studies by scholars such as Jonathan Brown and Fuat Sezgin as an important transition from oral tradition to written documentation. This study shows the relevance of Musnad Abu Dawud al-Tayalisi in the study of contemporary hadith and the need for critical analysis to maintain scientific validity.